Protective Effects of Adrenomedullin on Rat Cerebral Tissue After Transient Bilateral Common Carotid Artery Occlusion and Reperfusion - Kirisci,Mehmet (2020)
Abstract Objective: We aimed to investigate the protective effect of adrenomedullin (ADM) on cerebral tissue of rats with cerebral ischemia/reperfusion (I/R) injury. Methods: Thirty-two Wistar rats were randomized into four groups (n=8). In the I/R Group, bilateral common carotid arteries were clamped for 30 minutes and, subsequently, reperfused for 120 minutes. In the ADM Group, rats received 12 µg/kg of ADM. In the I/R+ADM Group, bilateral common carotid arteries were clamped for 30 minutes and, subsequently, the rats received 12 µg/ kg of ADM. Then, reperfusion was performed for 120 minutes. The Control Group underwent no procedure. Blood and brain tissue samples were collected for biochemical and histopathological analysis. Serum malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione peroxidase (GPx) were analysed. Brain tissue was evaluated histopathologically and neuronal cells were counted in five different fields, at a magnification of ×400. Results: Brain MDA in I/R Group was significantly higher than in ADM Group. Brain GPx and SOD in I/R+ADM Group were significantly higher than in I/R Group. The number of neurons was decreased in I/R Group compared to the Control Group. The number of neurons in I/R+ADM Group was significantly higher than in I/R Group, and lower than in Control Group. Apoptotic changes decreased significantly in I/R+ADM Group and the cell structure was similar in morphology compared to the Control Group. Conclusion: We demonstrated the cerebral protective effect of ADM in the rat model of cerebral I/R injury after bilateral carotid artery occlusion.